2008
DOI: 10.5547/issn0195-6574-ej-vol29-no3-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Demand in the European Household Sector

Abstract: This paper analyzes the residential natural gas demand in 12 European countries using a dynamic demand model, which allows for country-specific short- and long-run elasticity estimates. The own-price and income elasticities tend to be very inelastic in the short run, albeit with much greater responsiveness in the longer run. Our results support very limited technological substitution possibilities between different energy carriers in the short run. Furthermore, the results suggested structural differences of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 20 publications
(67 reference statements)
2
35
1
1
Order By: Relevance
“…For comparison, a review of studies by Espey and Espey (2004) found a mean shortrun elasticity of -0.35 (median -0.28) for electricity; a study by Asche et al (2008) found short run elasticities of household natural gas demand to be -0.25 or less; and a review of studies by Goodwin et al (2004) found a mean short-run elasticity for vehicle fuels of -0.25.…”
mentioning
confidence: 99%
“…For comparison, a review of studies by Espey and Espey (2004) found a mean shortrun elasticity of -0.35 (median -0.28) for electricity; a study by Asche et al (2008) found short run elasticities of household natural gas demand to be -0.25 or less; and a review of studies by Goodwin et al (2004) found a mean short-run elasticity for vehicle fuels of -0.25.…”
mentioning
confidence: 99%
“…The fact that natural gas demand tend to be seasonal (Asche et al, 2008) together with limited pipeline capacity, imply that seasonal peak load pricing can occur. While electricity markets experience extreme price peaks of short duration, the storability of natural gas suggests less extreme price movements in general and smoother seasonal pricing.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, demand for gas in Europe has more than doubled (Asche et al, 2008). This is largely due to increased use of natural gas in the power sector.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies including Baker and Blundell (1991) and Berkhout et al (2004) find that the elasticity of demand for gas in the residential sector is inelastic. We use an elasticity of -0.16, estimated by Asche, Nilsen and Tveterås (2008). We also carry out a sensitivity analysis in which we decrease the elasticity to -0.5 as this is the elasticity estimated for UK households (Baker and Blundell, 1991).…”
Section: Consumer Surplusmentioning
confidence: 99%